CPEC and Federalism: An Analysis - Hafeez Ullah Khan; Dr. Ijaz Khalid (Journal of Political Studies, 2018)
China Pakistan Economic Corridor (CPEC) is considered being the Game Changer not only for Pakistan but also for the whole of South Asian region, Central Asia and Middle East. CPEC is the main component of Chinese One Belt One Road (OBOR) initiative that was designed to provide alternative communications trade routes to continue the economic growth rate of Beijing which was lasted for last three decades. Apart from its international posture, Beijing also dreamed to reduce the gap between Eastern and Western China to address the question of sovereignty, to ensure the control of central government in Western China, that was threatened by the Eastern Turkistan Islamic Movement (ETIMI) in Xinjiang province. Pakistan also has reposed high expectations in CPEC in terms of politics, economics, social and strategic that still dominate the national and foreign policy since its inception. Among them, Pakistan has a federal form of government that divide the powers between center and provinces which is guaranteed by the written constitution of Pakistan. Being a twoway traffic, federalism could not flourished smoothly and did not provide the actual and fair distribution of state power between the centers and federating units since the establishment of current constitution in 1973. This piece of work examines and analyses the contribution of CPEC to the addressing of issues that dominated federalism in Pakistan since 1947 and broke the state into two parts in 1971. It will also elaborate that CPEC will strengthen the system by providing equal share to the provinces in the billion dollars project or it will widen the gap by ignoring the small provinces in their legitimate rights. The study finds that unlike China, by analyzing the two years outcomes of CPEC, serious issues were raised from the small provinces. Additionally, the study come to the conclusion that if the central government could not take the issues and grievances of already War torn parts of Pakistan (KP, Baluchistan) and Sind, CPEC will lose its essence to make Pakistan in real terms a federal republic state, the one that is envisaged in the constitution.